Non-edible Oil Cakes as a Novel Substrate for DPA Production and Augmenting Biocontrol Activity of Paecilomyces variotii - Arora, Kalpana; Sharma, Satyawati; Krishna, Suresh B. N.; Adam, Jamila K.; Kumar, Ashwani (Frontiers in Microbiology, 2017)
The present study investigated the use of waste non-edible oil cakes (Jatropha, Karanja, Neem and Mahua) as a substrate for the growth of Paecilomyces variotii and dipicolinic acid (DPA) production. Previous researches proved the efficacy of DPA in suppressing certain pathogens that are deleterious to the plants in the rhizosphere. DPA production was statistical optimized by amending non-edible oil cakes in growing media as nitrogen and sugars (Dextrose, Glucose and Lactose) as carbon source. Plackett-Burman design (PBD), indicated that Jatropha cake, Karanja cake and Dextrose were the most significant components (p<0.05) of the media and were further optimized using response surface methodology (RSM). Jatropha cake, Karanja cake and Dextrose at the concentration of 12.5 g/l, 4.5g/l and 10g/l, respectively, yielded 250 mg/l of DPA, which was 2.5 fold more than that obtained from basal medium. HPLC analysis of the optimized medium (peak at retention time of 30 min) confirmed the enhanced DPA production by P. variotii. The scanning electron microscopy (SEM) images showed that optimized medium impose a stress like condition (due to less C:N ratio) for the fungus and generated more spores as compared to the basal medium in which carbon source is easily available for the mycelial growth. The antimicrobial activity of the fungal extract was tested and found to be effective even at 10-2 dilution after 72 h against two plant pathogens, Fusarium oxysporum and Verticillium dahlia. Statistical experimental design of this study and the use of non-edible oil cakes as a substrate offer an efficient and viable approach for DPA production by P. variotii.